Formate/bicarbonate interconversion for safe hydrogen storage: A review. (March 2023) - Calabrese, M.; Russo, D.; di Benedetto, A.; Marotta, R.; Andreozzi, R.
Abstract: Formates are promising salts for hydrogen storage. They can be catalytically converted to bicarbonate at near-ambient conditions, and regenerated under moderate pressure for H2 uptake. Moreover, the system is completely safe, non-toxic, and easy to handle. Up to date, a few heterogeneous catalytic systems have been proposed to carry this transformation. However, many criticisms still have to be addressed, including reaction kinetics for high power applications, stability, cyclability, and supersaturated solutions to increase energetic density. In this work, a critical review of the state of art of such system is presented, highlighting theoretical limitations and applicative shortcomings, and giving perspective on critical issues to be addressed in future research. Despite the actual bottlenecks, the system is still scarcely explored and there is promising room for improvement. State-of-the-art catalytic systems could provide 72% energetic efficiency, that could be improved up to 90%. Graphical abstract: Image 1 Highlights: Formates are valid alternatives for safe H2 storage at near ambient conditions. Thermodynamics of homogeneous systems show volumetric density up to 1.4 MJ L -1 Catalyst were cycled up to 15 times with kinetics up to 8.87·10-2 mol L - 1 s - 1 . Supersaturated solutions/new catalysts can improve energy density/available power. State-of-the-art systems provide 72% energy efficiency improvable up to 90%.